Colloidal InSb Quantum Dots/Organic Integrated Bulk Heterojunction for Fast and Sensitive Near‐Infrared Photodetectors. Issue 4 (17th January 2022) - He, Miao; Xu, Zhuhua; Zhang, Si-Wei; Zhang, Meng; Wu, Chengcheng; Li, Baohua; Li, Jingzhou; Wang, Lai; Zhao, Shichao; Kang, Feiyu; Wei, Guodan
Abstract : It remains urgent to integrate conductive InSb colloidal quantum dots (CQDs) for sensitive and fast near‐infrared (NIR) photodetection applications. Herein, nanocrystallized InSb CQDs (<12 nm in diameter) have been successfully obtained via hot‐injection procedure, and demonstrated a very narrow absorption peak centered at 1406 nm with a full width at half maximum (FWHM) of 10.3 nm and a broader absorption peak at 1702 nm, indicating strong quantum‐confined effect. After integrating these InSb CQDs with [6, 6]‐phenyl C61 ‐butyric acid methyl ester (PCBM) and polymeric triphenyldiamine (poly( N, N ′‐diphenylben‐zidine diphenylether), poly‐TPD) bulk junction, the obtained Si/SiO2 /InSb CQDs:PCBM:poly‐TPD/Ag photodetector has reached long‐wavelength response up to 1400 nm, fast response time (<80 ms), and superior on/off ratio. In specific, charge carriers can be effectively transported due to favorable energy alignment and interpenetrating network formed in the inorganic/organic blend films. The work provides a new strategy to synthesize high‐quality InSb CQD and reveal its starting point toward low‐cost, practical, and sensitive next‐generation NIR detection. Abstract : Nanocrystallized InSb colloidal quantum dots (CQDs) (<12 nm in diameter) have been successfully obtained via hot‐injection procedure, and demonstrated a very narrow absorption peak centered at 1406 nm. The obtained colloidal InSb quantum dots/organic integrated photodetector is a fast and sensitive near‐infrared photodetector, with long‐wavelength response up to 1400 nm, fast response time (<80 ms), and superior on/off ratio.